1997
DOI: 10.1046/j.1464-410x.1997.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glycosaminoglycans in human prostate by high‐performance liquid chromatography

Abstract: Objective To investigate changes in glycosaminoglycan hyaluronic acid, were analysed qualitatively and quantitatively. The total amount of GAGs was (GAG) profiles in human prostatic tissue. Materials and methods Seventeen human prostatic increased in hyperplastic and cancerous prostates, with the predominant components being DS and Ch-6S samples were examined; five were normal, six hyperplastic and six were cancerous. Prostatic proteoglycans in these specimens. The Ch-S5DS ratio in cancerous prostate was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 4 publications
1
29
0
2
Order By: Relevance
“…Our previous studies illustrated that patients treated by radical prostatectomy for early stage (cT 1 -cT 2 ) cancer who showed high chondroitin sulfate concentration in the peritumoral stroma of the prostate had a significantly higher incidence of PSA failure than patients with low chondroitin sulfate concentration (14). Chondroitin sulfate levels in advanced (cT 4 ) prostate cancer tissues are very similar to the levels present in those early-stage prostate tumors that ultimately progressed, 12 suggesting that metastasis could be associated with increased chondroitin sulfate levels. Although chondroitin sulfate proteoglycans are widely distributed both on the surfaces of most cells and in the extracellular matrix, the structure and function of chondroitin sulfate side chains in malignant tissues have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our previous studies illustrated that patients treated by radical prostatectomy for early stage (cT 1 -cT 2 ) cancer who showed high chondroitin sulfate concentration in the peritumoral stroma of the prostate had a significantly higher incidence of PSA failure than patients with low chondroitin sulfate concentration (14). Chondroitin sulfate levels in advanced (cT 4 ) prostate cancer tissues are very similar to the levels present in those early-stage prostate tumors that ultimately progressed, 12 suggesting that metastasis could be associated with increased chondroitin sulfate levels. Although chondroitin sulfate proteoglycans are widely distributed both on the surfaces of most cells and in the extracellular matrix, the structure and function of chondroitin sulfate side chains in malignant tissues have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 82%
“…The concentration of chondroitin sulfate is greatly increased over normal tissue levels in several different malignancies (7)(8)(9)(10), including prostate cancer (11)(12)(13). Our previous studies illustrated that patients treated by radical prostatectomy for early stage (cT 1 -cT 2 ) cancer who showed high chondroitin sulfate concentration in the peritumoral stroma of the prostate had a significantly higher incidence of PSA failure than patients with low chondroitin sulfate concentration (14).…”
Section: Introductionmentioning
confidence: 99%
“…GAG production was previously recognized in prostatic stromal tissue [4,6,7,[10][11][12][13], and outside stromal tissues it has been recognized in the secretory products of white blood and tissue mast cells [14]. Furthermore, GAG production by epithelial cells has in the past been limited to their contribution of basement membrane material [15] and was not considered part of normal epithelial exocrine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Furthermore, high performance liquid chromatography analysis of glycosaminoglycans extracted from prostate cancer samples revealed that chondroitin-6-sulfate and dermatan sulfate were the predominantly upregulated components. 18 Indeed, elevated levels of sulfated chondroitin were reported to be associated with poorer disease outcome in early stage prostate cancer. 19,20 The biological activities of chondroitin sulfate, as well as its ability to bind to and interact with different growth factors and signaling molecules, are dependent on the presence of distinct sulfation motifs.…”
mentioning
confidence: 99%